Muscle strength in the oldest old and associated factors - Andréa Ferreira Cardoso; Aline Rodrigues Barbosa; Raildo da Silva Coqueiro (Colégio Brasileiro de Ciências do Esporte, 2013)
The objective of this cross-sectional household-based study was to investigate the factors associated with muscle strength in the oldest old (≥ 80 years) living in a rural area, of southern Brazil. We interviewed a total of 56 men (85.0 ± 4.4 y) and 78 women (84.5 ± 4.8 y). Prevalence of poor performance in the handgrip test (isometric strength) was 39.2% and was associated with illiteracy, underweight, and cognitive deficit. Poor performance in the "chair stand" test (lower body strength/physical function) was observed in 48.5% of the elderly and was more prevalent in men and among those who consumed more alcoholic drink/week. The results may be useful as indicators to public health surveillance, and to the development of prevention and intervention actions.